Micromixing Models for PDF Simulations of Turbulent Premixed Flames. Issue 8 (3rd August 2019) - Ren, Zhuyin; Kuron, Mike; Zhao, Xinyu; Lu, Tianfeng; Hawkes, Evatt; Kolla, Hemanth; Chen, Jacqueline H.
ABSTRACT: Transported probability density function (TPDF) methods are attractive for modeling turbulent flames as the highly nonlinear chemical reactions appear in closed form. The ability of the TPDF methods to capture complex phenomena such as extinction and re-ignition has been well demonstrated for turbulent non-premixed flames. However challenges remain when applying the TPDF methods to turbulent premixed flames, for which modeling molecular diffusion is difficult because the local species gradients may be strongly influenced by chemical reactions. The specification of a constant mechanical-to-scalar timescale ratio to relate the scalar mixing timescale to the turbulence timescale is questionable for premixed flames in the flamelet regime. In this paper, recent progress on scalar mixing is reviewed with particular focus on the analysis and modeling of the scalar mixing timescales in turbulent premixed flames using direct numerical simulation (DNS) datasets. The scalar dissipation rate of the progress variable from temporally evolving turbulent lean premixed H2-air flames in the thin reaction zone regime is analyzed using the chemical explosive mode analysis to understand its dependence on combustion modes and transient flame features. Moreover, models for the mixing timescale of the progress variable are discussed, with a focus on a recently developed hybrid mixing timescale model. This work concludes with a discussion on modeling differential diffusion in turbulent premixed flames.